An alternative description of paleo-astrogeophysics process and origin of Earth based on Low Temperature Physics: Including an outline to mitigate increasing Earth surface temperature - Christianto, Victor; Suria, Isak (Sekolah Tinggi Teologi Satyabhakti, East Java, 2024)
Dalam artikel sebelumnya di Jurnal BPAS Geology Section, denganjudul: “How Shannon Entropy perspective provides link amongexponential data growth, average temperature of the Earth, decliningEarth magnetic field, and global consciousness” (BPAS Section F,Geology, 2019), penulis membahas antara lain data sunspotsepertinya menunjukkan bahwa Matahari kemungkinan akanmemasuki Maunder Minimum, yang dapat berarti rendahnyaaktivitas Matahari kemungkinan dapat menyebabkan rendahnyasuhu di Bumi, sementara itu kita mengalami suhu permukaan Bumiyang semakin tinggi. Kita juga harus mengingat perubahan iklim global yang akan terjadi dalam waktu dekat (cf. Toffler, The Ecospasm report, 1975). Fenomena ini kemudian membuat kamibertanya: apa yang dapat kita lakukan sebagai manusia di Bumiuntuk menunda atau menghindari memburuknya suhu pendinginanBumi di tahun-tahun mendatang? Kami pikir ini adalah masalahyang lebih mendesak dan merupakan bahaya nyata saat ini yang kitahadapi di Bumi. Seperti yang telah kami bahas sebelumnya, di sinikita akan membahas pendekatan fisika suhu rendah terhadap alamsemesta awal bersama dengan bumi ini, yang tampaknya terkaitdengan proses paleo-astrogeologi Bumi kita, serta model interaksiMatahari-Bumi dalam kaitannya dengan entropi Shannon. Karenaentropi Shannon dapat dinyatakan sebagai bit informasi, maka iniberarti kita mungkin dapat melakukan sesuatu terhadap suhu bumidengan mengontrol jumlah transfer dan penyimpanan informasi dibumi. Alternatif yang dapat dipertimbangkan dalam hal ini adalahdengan memantau dan mendinginkan perikanan laut dalam, karenabeberapa jenis ikan laut dalam kemungkinan besar akanmempengaruhi suhu laut global, dan kemudian suhu permukaanglobal cenderung meningkat. Abstract In a previous article in a Journal, with title: “How Shannon Entropyperspective provides link among exponential data growth, averagetemperature of the Earth, declining Earth magnetic field, and globalconsciousness” (BPAS Section F, Geology, 2019), we discussedamong other things that the sunspot data seems to indicate that theSun is likely to enter Maunder Minimum, then it will mean that low Sun activity may cause low temperature in Earth, while in themeantime we experience increasingly high Earth surfacetemperature. We shall also keep in mind impending global climatechanges in the near future (cf. Toffler, The Eco-spasm report, 1975).This phenomenon then causes us to ask: what can we do as humanbeing in Earth to postpone or avoid the worsening situation in termsof Earth cooling temperature in the coming years? We think this is amore pressing problem for the real and present danger that we arefacing in the Earth. As we discussed earlier, we would discuss here alow temperature physics approach to early Universe along with thisearth, which seems to be linked to paleo-astrogeological process ofour Earth, along with a model Sun-Earth interaction in terms ofShannon entropy. Since Shannon entropy can be expressed as bits ofinformation, then it would mean that perhaps we can do somethingwith Earth temperature by controlling the amount of informationtransfer and storage in the Earth. An alternative way that can beconsidered in this regard is to monitor and cool deep-ocean fisheries,because several kind of deep-sea fishes are likely to affect the globalsea temperature, and then the global surface temperature tends toincrease.